2009
DOI: 10.1007/s00508-009-1229-0
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocyte counts in mice after the administration of papaya leaf suspension

Abstract: Following up a popular use of crude leaf preparations from Carica papaya for the treatment of dengue infections, a suspension of powdered Carica papaya leaves in palm oil has been investigated for its effect on thrombocyte counts in mice, administering by gavage 15 mg of powdered leaves per kg body weight to 5 mice. Equal numbers of animals received corresponding volumes of either palm oil alone or physiological saline solution. Thrombocyte counts before and at 1, 2, 4, 8, 10, 12, 24, 48 and 72 hours after dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 12 publications
3
22
2
Order By: Relevance
“…A study in mice found an increase in thrombocyte counts in mice administered 15 mg of powdered papaya leaves/kg body weight between 1 and 12hrs following dosing [13]. Another study found that the C. papaya leaf aqueous extract at concentrations of 400 mg/kg and 800 mg/kg significantly increased the platelet counts in cyclophosphamide-induced thrombocytopenic rat model.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in mice found an increase in thrombocyte counts in mice administered 15 mg of powdered papaya leaves/kg body weight between 1 and 12hrs following dosing [13]. Another study found that the C. papaya leaf aqueous extract at concentrations of 400 mg/kg and 800 mg/kg significantly increased the platelet counts in cyclophosphamide-induced thrombocytopenic rat model.…”
Section: Animal Studiesmentioning
confidence: 99%
“…It also reduced the clotting time in the treated rats [14]. Another study in mice reported that C. papaya substances responsible for the release and/or production of thrombocytes [15].…”
Section: Animal Studiesmentioning
confidence: 99%
“…[13] Another study found that the C. papaya leaf aqueous extract at concentrations of 400 mg/kg and 800 mg/kg significantly increased the platelet counts in cyclophosphamide-induced thrombocytopenic rat model. It also reduced the clotting time in the treated rats.…”
Section: Studies In Animalsmentioning
confidence: 99%
“…A study was aimed to investigate the potential role of fresh Carica papaya leaf extract on hematological and biochemical parameters and toxicological changes in a murine model. 13 Fresh C. papaya leaf extract significantly increased the platelet and RBC counts in the test group as compared to controls. 15 Therefore, it is very important to identify those phytochemicals of C. papaya leaves as it can be recommended to be used as a medication to boost thrombopoiesis and erythropoiesis in humans and in animals in which these cell lineages have been compromised.…”
mentioning
confidence: 99%
“…12 The leaf is considered non-toxic as its lethal dose is >15 g/kg body weight. 13 Recent studies showed that C. papaya leaf extract has potential anti-sickling (inhibition of sickle cell formation) properties. 14 The capacity of papaya leaf extract to reverse the lowering of blood cells, especially platelets, is gaining attention in recent times.…”
mentioning
confidence: 99%